2018
DOI: 10.3390/healthcare6030084
|View full text |Cite
|
Sign up to set email alerts
|

Lyme Disease Transmission Risk: Seasonal Variation in the Built Environment

Abstract: Seasonal variation in spatial distribution and pathogen prevalence of Borrelia burgdorferi in blacklegged ticks (Ixodes scapularis) influences human population risk of Lyme disease in peri-urban built environments. Parks, gardens, playgrounds, school campuses and neighborhoods represent a significant risk for Lyme disease transmission. From June 2012 through May 2014, ticks were collected using 1 m2 corduroy cloths dragged over low-lying vegetation parallel to walkways with high human foot traffic. DNA was ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…We found a higher abundance of nymphs early in the year, as expected based on tick phenology 29,30 . Interestingly, we also found a higher infection prevalence by B. burgdorferi late in the year, which is similar to findings from another study in Europe 31 , although this trend is not consistently observed in all regions or all years 32 . Our results support a general pattern seen throughout the range of I. scapularis , with the Spring and Fall seasons posing different levels of Lyme disease risk owing to changes in environmental risk and human exposure.…”
Section: Discussionsupporting
confidence: 89%
“…We found a higher abundance of nymphs early in the year, as expected based on tick phenology 29,30 . Interestingly, we also found a higher infection prevalence by B. burgdorferi late in the year, which is similar to findings from another study in Europe 31 , although this trend is not consistently observed in all regions or all years 32 . Our results support a general pattern seen throughout the range of I. scapularis , with the Spring and Fall seasons posing different levels of Lyme disease risk owing to changes in environmental risk and human exposure.…”
Section: Discussionsupporting
confidence: 89%
“…Regardless, nymphal size would make it virtually impossible to mark and observe ticks in the same manner as adults in the present study. Although nymphs are considered to be responsible for much of the transmission of B. burgdorferi to humans in North America (Fish, ), adult I. scapularis should not be dismissed as a significant contributor – they are nearly twice as infected (45.5% of adults compared to 27.5% of nymphs) (Roome et al ., ); are host‐seeking a greater proportion of the year (spring and fall for adults compared to summer for nymphs) (Roome et al ., ); and, as demonstrated by this experiment, can actively and successfully locate stationary hosts.…”
Section: Discussionmentioning
confidence: 99%
“…The transition of adult I. scapularis ticks to an active‐search approach would likely increase the foraging success of ticks near host animals that have stopped to rest/sleep or feed. As ticks are increasingly found in built environments often constructed for the purpose of human congregation (Roome et al ., ), awareness is required for outdoor activities that involve remaining stationary (napping, picnicking, reading, etc.) in areas where ticks may be present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial communities within ticks are also known to be influenced by environmental conditions, notably through the modification of tick density, tick behavior, or the vector-host interactions ( 28 30 ). For example, B. burgdorferi is most likely found at lower altitudes ( 27 ), infects more ticks collected in forests than in pastures ( 29 , 31 ), and may be favored by forest fragmentation ( 31 , 32 ), whereas Rickettsia bacteria may be more prevalent in ticks in pasture sites showing a shrubby vegetation and a medium forest fragmentation ( 31 ). Environmental factors might provide us with critical information regarding bacterial distribution and thus potential threats to humans.…”
Section: Introductionmentioning
confidence: 99%